MANAJEMEN PENGELOLAAN SAMPAH DI KECAMATAN TEMBALANG - Nigiana P.P, Jayanti; Lestari, Endang; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Population growth that high in the region or country can will certainly pose a problem various environment. One is the problem of waste. In the issue of garbage there must be participation of the people in it. Participation care it must be improved so that the public rubbish bins regarding the issue be resolved easily. Empower activity community and develop it for review to combat the waste problem and the Environment made the more society active role and have sensitive hearts gainst approximately circumstances. Management in Waste Management in Semarang District have purposes: (1) to describe and analyze the management of waste management in the District Tembalang that done, (2) knowingthe obtacles encountered in Waste management in Semarang District Tembalang.Type of this research is a descriptive, the research aims to review describe, explain, record, analyze and interpret the present condition that happened or no. Based on the result of research, one form of waste management with give contribution activity managing resourses form trash that begins with the training given posted district Tembalang then implement on waste management activities with garbage sorting and recycling waste being items that can be reused. Management of waste management in the District Tembalang have been executed nice, but it is still not optimal , so it is necessary to improve in some aspects , such as the handling of the various obstacles encountered in the waste management in District Tembalang .